ok so
4+3x=3x+15/x+3......................the first thing we need to do is multiply by x+3 so
(4+3x)(x+3)=3x+15
4x+12+3x^2+9x=3x+15
3x^2+13x+12=3x+15
3x^2+10x-3=0.................................... know we need to use the quadratic equation
a=3
b=10
c=-3
x1,2=-b+or-sqrD/2a
x1,2=-10+or- sqr10^2-4*(-3)*3/6
x1,2=-10+or-sqr64/6..........................sqr64=8
x1,2=-10+or-8/6
x1=-10-8/6=-18/6=-3
x2=-10+8/6=-2/6=-1/3
x1=-3
x2=-1/3
hope i helped^^

Answer #4 | 11/02 2014 08:03

step by step solutions:
http://symbolab.com/solver/equation-calculator/4%2B3x%3D%20%5Cfrac%7B3(x%2B5)%7D%7Bx%2B3%7D%20
hope this helps

Answer #1| 11/02 2014 06:33